2020
DOI: 10.1103/physrevlett.125.237005
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Doping Evolution of Superconductivity and Quasiparticle Interference in Bi2Sr2Ca2Cu3

Abstract: We use scanning tunneling microscopy to investigate Bi2Sr2Ca2Cu3O10+δ trilayer cuprates from the optimally doped to overdoped regime. We find that the two distinct superconducting gaps from the inner and outer CuO2 planes both decrease rapidly with doping, in sharp contrast to the nearly constant TC. Spectroscopic imaging reveals the absence of quasiparticle interference in the antinodal region of overdoped samples, showing an opposite trend to that in single-and double-layer compounds. We propose that the exi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…Here the scattering mainly occurs between the hot spots of the banana-shaped equal-energy contours of the Bogoliubov quasiparticles 28 , 30 , 31 . With increasing doping levels, the Bogoliubov QPI is gradually weakened, as reported by earlier studies on overdoped cuprates 32 . For the slightly overdoped OD-28K sample in Fig.…”
Section: Resultssupporting
confidence: 80%
“…Here the scattering mainly occurs between the hot spots of the banana-shaped equal-energy contours of the Bogoliubov quasiparticles 28 , 30 , 31 . With increasing doping levels, the Bogoliubov QPI is gradually weakened, as reported by earlier studies on overdoped cuprates 32 . For the slightly overdoped OD-28K sample in Fig.…”
Section: Resultssupporting
confidence: 80%
“…Recent scanning tunneling microscopy (STM) studies ( 5 ) have shown that the superconducting gap of Bi-2223 decreases monotonously with p in the overdoped regime. Unexpectedly, the T c in this doping range exhibits a plateau rather than a continuous drop, most likely owing to the existence of two types of inequivalent CuO 2 planes ( 6 , 7 ). By contrast, the Bi-2223 system provides an ideal platform for investigating the evolution of T c,max with n and the physical parameters that control T c,max .…”
mentioning
confidence: 87%